Analisis Kebijakan Donor Darah Dan Implementasi Program Rekrutmen Donor Di Unit Donor Darah (UDD PMI) Kota Pontianak - Ria Risti Komala Dewi; Martha Irene Kartasurya; Atik Mawarni (Jurnal Manajemen Kesehatan Indonesia, 2016)
The availability of blood in Blood Donor Unit of Indonesian Red Cross (BDU-IRC) cannot fulfil the necessity of blood in Pontianak City for every year. Until the year 2014, there was only 37.3% of the total blood demand that could be provided. The aim of this study was to analyse problems of resource, attitude and commitment, a bureaucracy structure, communication, and social condition in implementing the blood donor recruitment program in BDU-IRC in Pontianak City.This was an observational study using a descriptive-qualitative design. Data were collected using methods of indepth interview, Focus Group Discussion, and observation. Main informants consisted of five P2D2S officers (a head of department and four staffs of P2D2S). Informants for triangulation purpose were 22 persons consisted of two decision makers, (a head of BDU and a deputy head of IRC), five coordinators of KDD, five persons of DDS, five persons of DDP, five citizen of Pontianak City. Data were analysed using content analysis.The results of this research showed that resource was quantitatively sufficient but it was qualitatively insufficient, particularly willingness of the officers in implementing their duties. Amount of budget was limited. There were a poor attitude and lack of commitment of the officers due to lack of willingness and low motivation to implement their duties in accordance with available regulations and goals. Not all the implementation was referred to Standard Operating Procedure released by the main office of IRC because the officers assumed that they had understood the ways to recruit blood donor. Communication was unclear and inconsistent. Support from blood donor groups was not optimal due to lack of attention and support from the program implementer such as supervising, providing rewards, and providing a supporting facility. In conclusion, the implementation of the blood donor recruitment program have not been well implemented. BDU-IRC needs to improve a competency of the officers by conducting training for untrained officers. The unit also needs to conduct a meeting to arrange a work program and a budget allocation annually. In addition, a community needs to be proactively asked to provide their blood to the IRC.